2017
DOI: 10.3390/nu9030223
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants for Healthy Skin: The Emerging Role of Aryl Hydrocarbon Receptors and Nuclear Factor-Erythroid 2-Related Factor-2

Abstract: Skin is the outermost part of the body and is, thus, inevitably exposed to UV rays and environmental pollutants. Oxidative stress by these hazardous factors accelerates skin aging and induces skin inflammation and carcinogenesis. Aryl hydrocarbon receptors (AHRs) are chemical sensors that are abundantly expressed in epidermal keratinocytes and mediate the production of reactive oxygen species. To neutralize or minimize oxidative stress, the keratinocytes also express nuclear factor-erythroid 2-related factor-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
101
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 62 publications
0
101
1
Order By: Relevance
“…AHR is a xenobiotic chemical sensor that is abundantly expressed in barrier-forming epithelial tissues such as skin, trachea, and intestine [3,[19][20][21][22][23]. Various xenobiotic and natural compounds such as dioxins, dietary polyphenols including flavonoids, and microbiota-derived factors can activate AHR and upregulate CYP1A1 expression leading to the induction of oxidant and/or antioxidant signaling pathways in a ligand-dependent manner [3,5,24]. AHR is also an important regulator of the development and function of both innate and adaptive immune cells and is indispensable for the maturation of intestinal immunity [5,21,22,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…AHR is a xenobiotic chemical sensor that is abundantly expressed in barrier-forming epithelial tissues such as skin, trachea, and intestine [3,[19][20][21][22][23]. Various xenobiotic and natural compounds such as dioxins, dietary polyphenols including flavonoids, and microbiota-derived factors can activate AHR and upregulate CYP1A1 expression leading to the induction of oxidant and/or antioxidant signaling pathways in a ligand-dependent manner [3,5,24]. AHR is also an important regulator of the development and function of both innate and adaptive immune cells and is indispensable for the maturation of intestinal immunity [5,21,22,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirmed that RAPA reduced ROS accumulation by restoring the activity of antioxidants, such as SOD, GPx, and CAT, after UVB irradiation. Several studies have reported that RAPA can increase the level of resistance to oxidation by activating the antioxidant transcription factor Nrf2, which increases the expression of antioxidants [50, 51]. RAPA pretreatment also enhanced the levels of endogenous antioxidants in photoaged cells, suggesting that RAPA had the ability to regulate the cellular redox system at the molecular level by activating Nrf2.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it was shown that UVB-induced damage is mediated almost solely by ROS generation in the skin [30, 31]. In addition, several publications reported that UV radiation can be attenuated by activating the Nrf2 signaling pathway [32-36].…”
Section: Resultsmentioning
confidence: 99%
“…Besides serving as classical sources for oxidative stress in skin mitochondrial functions, physiological enzymatic activity, hyperglycemia, and overactivation of the immune system, skin is also exposed to external stimuli, such as ionization and UV radiation, environmental pollutants, contact allergens, and topically used drugs [31]. The use of enzymatic antioxidants, combined with classical antioxidant molecules (glutathione, vitamin E, and vitamin C), is extremely important for skin protection against oxidative stress.…”
Section: Resultsmentioning
confidence: 99%